Parent Perspectives on Speech-Language Therapy Delivered via Telehealth During and After the Pandemic - Fromm, Caitlin (My University, 2024)
Abstract Telehealth is the virtual delivery of services using video platforms that allow patients to be provided with various services remotely. It is crucial to understand the successes and barriers of speech-language therapy via telemedicine, and why or why not parents choose to continue with this method of delivery. Current research has explored what this has looked like in other countries, as well as in other disciplines. Teletherapy for speech-language services in the US has yet to be explored through the eyes of parent surveys. Three study objectives were written before the start of the survey; understand the opinions and level of satisfaction parents experienced related to speech-language therapy via telehealth during the COVID-19 pandemic, determine what factors led to parents continuing or discontinuing telehealth as their mode of delivery, and analyze what successes and barriers there were to the use of speech-language therapy via telehealth during the COVID-19 pandemic. This survey will include parents of children who received speech-language therapy via telehealth during the COVID-19 pandemic. The survey was developed using procedures outlined by the commonly accepted stages of a questionnaire development process. Dissemination of the survey occurred through social media platforms and field-specific forums. Data was collected from July 2023 to November 2023. Ninety-five participants began the survey and 60 participants completed items corresponding to teletherapy. Results from this survey have the potential to identify facilitators and barriers within telehealth and allow speech-language pathologists (SLPs) to reflect upon successes and make improvements to area(s) of concern within their practice. Parent input allows SLPs to adapt appropriately. We want to use the resulting themes to better the practice of speech-language therapy via telehealth.
Keywords: Telehealth; Speech-Language Therapy; COVID-19